SISTEM INFORMASI PERPUSTAKAAN STMIK NEUMANN INDONESIA DENGAN METODE WATERFALL - Indri Yani Br Tarigan; Bersama Sinuraya (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2019)
In the Christian STMIK library of Neumann Indonesia, in the process of borrowing books that alwaysexperience problems or problems, namely in the process of borrowing books, they are still donemanually and have not used the system on the computer. For this reason, a system is needed tofacilitate the processing of book data and the loan process into a system that is fast, accurate, andprecise by using an active active library card. And the visitor's data collection system uses the QRCode as a tool to scan active library cards that use laptop cameras. So in this case, the authordesigned a system with the PHP programming language. The results of this study indicate that the useof the visitor system using the QR Code helps library staff in the Student data collection process.